Enduring financial debt: an Islamic perspective - Bensaid, Benaouda (IDOSI Publications, 2013)
This paper investigates some of the major concepts on indebtedness in Islam while shedding light on the spiritual and moral implications associated with indebtedness, for both debtors and lenders. The research further shows that Islam capitalizes on the spiritual and moral reservoir of Muslims in dealing with life financial difficulties and that it further sets a number of religious measures that not only ease the emotional and social distress of debtors, but also protect the rights of lenders while sustaining communal piety, dignity and responsibility.